Interface engineering of the photoelectrochemical performance of Ni-oxide-coated n-Si photoanodes by atomic-layer deposition of ultrathin films of cobalt oxide1. Issue 9 (26th September 2015) - Zhou, Xinghao; Liu, Rui; Sun, Ke; Friedrich, Dennis; McDowell, Matthew T.; Yang, Fan; Omelchenko, Stefan T.; Saadi, Fadl H.; Nielander, Adam C.; Yalamanchili, Sisir; Papadantonakis, Kimberly M.; Brunschwig, Bruce S.; et al.
<x xml:space="preserve">Abstract</x> Interfacial CoOx layers provide a route to stable, high-performance Si photoanodes for water splitting, without requiring np+ homojunctions.